Agreement of International cooperation between the Fundação Minerva – Cultura – Ensino e Investigação Científica / Universidades Lusíada and the Athens Institute for Education and Research - Fundação Minerva – Cultura – Ensino e Investigação Científica (2019)
- To organize international conferences; - To cooperate in publications; - To cooperate in scientific research; - To organize short-term courses; - To organize workshops.